Patterns, relevance and predictors of heart failure dyadic symptom appraisal. (October 2017) - Lee, Christopher S; Mudd, James O; Auld, Jonathan; Gelow, Jill M; Hiatt, Shirin O; Chien, Christopher V; Bidwell, Julie T; Lyons, Karen S
Background: Caregivers are thought to play a major role in helping patients first appraise and then respond to heart failure (HF) symptoms. Aims: The aims of this study were to: (a) characterise distinct patterns of HF patient–caregiver dyads with respect to symptom appraisal; and (b) link dyadic symptom appraisal to contributions to self-care and caregiver strain. Methods and results: A cross-sectional dyadic descriptive design was used to capture patient and caregiver appraisal of patient HF symptoms (i.e. dyspnoea, fatigue, pain and anxiety). Contributions to self-care were measured using patient and caregiver versions of the Self-Care of Heart Failure Index and the European Heart Failure Self-care Behaviour Scale. Caregiver strain was measured using the Multidimensional Caregiver Strain Index. Multilevel and latent class mixture modelling (LCMM) were used to examine distinct patterns of symptom appraisal. Two patterns of dyadic symptom appraisal were identified: one pattern ( n = 24; 38.7%) wherein caregivers appraised patients' symptoms as being significantly worse than did the patient (labelled as 'Caregiver > Patient'); and a second pattern ( n = 38; 61.3%) wherein patients appraised their symptoms similar to or worse than that as perceived by their caregiver (labelled as 'Patient ⩾ Caregiver'). Dyads in the Caregiver > Patient pattern of symptom appraisal reported much better contributions to self-care (symptom response behaviours only), but also greater caregiver strain, compared with dyads in the Patient ⩾ Caregiver pattern. Greater patient depression and older caregiver age were significant determinants of fitting the Patient ⩾ Caregiver pattern. Conclusion: Differences in how HF patients and caregivers appraise symptoms together must be taken into consideration when examining contributions to HF care and caregiver outcomes.